The Impact of AI and IoT-Driven Systems on the Social and Psychological Aspects of Employee Management in the Banking Sector - Gulati, Kamal; Unhelkar, Bhuvan; Khatri, Eti; Abdul, Sikandar Mohd.; Choubey, Somya; Patni, Ity (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Artificial intelligence (AI) and the Internet of Things (IoT) are highly disruptive, having a profound impact on the work and life of every individual. This impact is escalating rapidly with the advent of newer chatbots, analytical tools and user interfaces. Employee management is a major area of impact. AI and IoT automate routine tasks, optimize decision-making and reduce decision risks for employees and their managers. This study reports on the significant impact of AI and IoT based systems on the social and psychological aspects of employee management. This study is based on a survey of 200 respondents from the banking sector using direct random sampling.